Particle characteristics of microplastics contaminating the mussel Mytilus edulis and their surrounding environments. (September 2019) - Scott, Nicholas; Porter, Adam; Santillo, David; Simpson, Holly; Lloyd-Williams, Sophie; Lewis, Ceri
Abstract: We investigated the environmental partitioning and particle characteristics of macro-, meso- and microplastics and their uptake into the mussel, Mytilus edulis . Sediment samples, overlying seawater and mussels from 9 intertidal locations in the South West of England were analysed for abundance and type of microplastic. Micro- and mesoplastic-like particles were found in 88.5% of the 269 mussels sampled, ranging from 1.43 to 7.64 items per mussel. Of these plastic particles, 70.9% were identified as semi-synthetic (mainly modified-cellulose). Mussel microplastic abundance, but not polymer type, was correlated with that of their surrounding sediment, but not with sea-surface microplastic concentration or mussel size for our study sites. We found significant differences in the relative abundance of polymer types and particle sizes between seawater, sediment, and mussels, with mussels over-representing modified-cellulose fibre abundance but under-representing polyvinyl. Mussels contained significantly smaller plastic fragments than their surrounding sediment and shorter fibres than their overlying seawater. Highlights: Micro- and mesoplastic-like particles were found in 88.5% of mussels sampled. Relative abundance of polymer types and sizes between seawater, sediment, and mussels differed. Mussels contained a higher proportion of modified-cellulose fibres than the seawater. Polyvinyl was under-represented in mussels compared to their environment. Beach macro- and microplastics differed in polymer composition.